2021
DOI: 10.3390/nu13072345
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Foods Associated with Sodium and Potassium Intake in Japanese Youths Using the Brief-Type Self-Administered Diet History Questionnaire

Abstract: The identification of sodium and potassium intake in youths is an important step to preventing the increase of blood pressure in childhood. We examined food intake and estimated mineral intake using a brief-type self-administered diet history questionnaire (BDHQ) to test its validity as a comparison with urinary excretion in Japanese youths. The subjects were 5th and 8th graders (n = 2377), who completed the BDHQ and permitted the use of their overnight urine specimens. Sodium intake was poorly associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Moreover, participants in the Hypertensive group had the highest intake of sodium (Na) and salt (NaCl), 5082.4 mg/day and 12.8 g/day, respectively, which was higher than the Japanese Society of Hypertension′s recommendation of 6.0 g/day for hypertensive individuals [ 5 ]. However, because the BDHQ was designed to evaluate Japanese dietary habits and was not specific for sodium intake, we were unable to establish the relationship between salt intake, sodium intake, and hypertension in this study [ 57 ]. The current study considered that the easy-to-chew foods preferred by the older Japanese adults were processed foods with high salt content [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, participants in the Hypertensive group had the highest intake of sodium (Na) and salt (NaCl), 5082.4 mg/day and 12.8 g/day, respectively, which was higher than the Japanese Society of Hypertension′s recommendation of 6.0 g/day for hypertensive individuals [ 5 ]. However, because the BDHQ was designed to evaluate Japanese dietary habits and was not specific for sodium intake, we were unable to establish the relationship between salt intake, sodium intake, and hypertension in this study [ 57 ]. The current study considered that the easy-to-chew foods preferred by the older Japanese adults were processed foods with high salt content [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we calculated the sodium-to-potassium ratio from the quantities of sodium and potassium intake from the BDHQ data [ 40 ]. Although this has not been validated yet, previous studies have reported that the high potassium intake or low sodium-to-potassium ratio may have beneficial possibilities for BP [ 57 ]. Daily alcohol consumption was calculated as a part of the BDHQ [ 35 , 37 ].…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar to other food frequency questionnaires, the BDHQ is vulnerable to measurement errors and is weak in estimating nutrients from foods that have not been investigated. Although sodium intake estimated from the BDHQ was barely associated with urinary sodium excretion as an intake biomarker, the sodium-to-potassium ratio from the BDHQ was significantly associated with the urinary ratio [ 30 ]. Furthermore, the sodium-to-potassium ratio was more closely associated with blood pressure than sodium intake in previous studies in youths [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The correlation coefficients between the estimates from the single BDHQ for adults and 16-day dietary records were 0.17–0.66 (Spearman correlation) for cereals, sugar and confectionaries, vegetables, potatoes, fruits, fish, meat, egg, dairy products, and non-alcoholic beverages [ 26 ]; 0.35–0.64 (Pearson correlation) for protein, fat, and carbohydrate; 0.44–0.66 (Pearson correlation) for sodium, potassium, calcium, magnesium, and iron; and 0.42–0.63 (Pearson correlation) for beta-carotene equivalent, and vitamin C [ 27 ]. Spearman correlation coefficients with corresponding biomarkers in adolescents were 0.26–0.31 for serum carotenoids; 0.22–0.48 for red blood corpuscle marine omega-3 polyunsaturated fatty acids [ 28 ]; 0.11–0.30 for urinary nitrogen [ 29 ]; and 0.05 for sodium; 0.11 for potassium; and 0.10 for the sodium-to-potassium ratio [ 30 ]. Plausible responders were considered to have energy intake ≥0.5 and ≤1.5 times of age- and sex-specific estimated energy requirements for low and high physical activity levels (PALs), respectively [ 31 ].…”
Section: Methodsmentioning
confidence: 99%